Al-‘Ijāz al-Lughawiy fī al-Qur’ān ‘inda Badīuzzamān - Sujiat Zubaidi Saleh; Inayatul Maula (Universitas Darussalam Gontor, 2018)
Majority of Orientalists who focuses on Qur’anic Studies dominates a number of critical views ‎concerning the originality of al-Qur’an. Those ideas are: the disarrangement of Qur’anic verses; ‎even they believe in that verses are in confusion, the absence of interrelation between topics within ‎it, the lack of scientific writing structure, and some of them argue that al-Qur’an is precisely a ‎consolidation between words of Muhammad and not a divine revelation. Even though those ideas ‎are not true. If al-Qur’an is analyzed carefully utilizing scientific tools such as Arabic, the ‎privileges (I’jāz) of al-Qur’an will be founded in many of its sides. One of them is language ‎privileges which is also familiar as I’jāz lughawy. Badiuzzaman Said Nursi, a reformer Muslim ‎scholar in his age revealed the beauty, harmony, and privileges of language in al-Qur’an. This ‎paper will discuss Nursi’s thought about I’jāz Lughawiy in al-Qur’an including four main elements, those are balāghah and faṣāḥaḥ, structure of text and grammar, the secret of muqāṭa’ah, altogether ‎with the word repetitions in al-Qur’an.‎